Maffucci’s Syndrome –a Case Report of Rare Connective Tissue Disorder (Bangladesh Journal of Nuclear Medicine, 2018)
Maffucci’s syndrome comprises of multiple venous malformations in combination with dyschondroplasia and a variety of cutaneous, vascular, chondro-osseous and other benign and malignant mesodermal growths. This report describes the case of a 20 -year-male patient with a clinical diagnosis of Maffucci syndrome with multiple lobulated sof tissue swelling with phleboliths in left upper and lower limbs. Significant findings were presence of multiple haemangiomas, enchondromas and pathological fractures- those were evaluated by X-ray, skeletal scintigraphy and ultrasound. Skeletal scintigraphy play an important role to see the extent of the disease.Early detection and surgical management of these tumors form the basis of its treatment and desirable outcome.Bangladesh J. Nuclear Med. 20(1): 67-69, January 2017